PENGARUH KOMUNIKASI, MOTIVASI DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI - Misrawati, Misrawati; Sophian, Sophan (Ensiklopedia Education Review, 2025)
Abstract: The purpose of this research is to axamine the influence of communication variables on employee performance in the Siberut National Park Office. To test the influence of motivation variables on employee performance in the Siberut Padang National Park Office. To test the influence of communication variables on employee performance in the Siberut Padang National Park Office. Data were colleted through distributing questionnaires to 40 respondents using saturated sampling techniques,where all members of the population were sampled, using instrument tests (validity tests and reliability tests), descriptive analysis,classical assumption tests (normality tests, multicolinearity tests and heteroscedasticity tets) mulptiple linear regression and t tets, with the help of the SPSS application. The results of the research show that commuication has a positive and significant effect on employee performance in at the Siberut Padang National Park Office in Padang, motivation has a positive and significant effect on employee performance in at the Siberut National Park Office in Padang. And  job satisfation has a positive and significant effect on employee perforance in at the Siberut Padang National Park Office, which means the first hyphotesis is accepted, the second hypotesis is accepted and the third hypotesis is accepted.Keywords:  Communication, Motivation, Job Satisfaction And Employee Performance.